2010
DOI: 10.1021/jf904575k
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mab-Based Heterologous Immunoassay for the Broad-Selective Determination of Organophosphorus Pesticides

Abstract: A broad-selective monoclonal antibody (Mab) for organophosphorus (OP) pesticides was raised using heterologous indirect enzyme-linked immunosorbent assay (ELISA) to screen hybridomas. On the basis of this Mab, five coating antigens were used to develop homologous and heterologous indirect competitive ELISAs. With the most suitable competitor, a sensitive and broad-selective ELISA was developed. The IC 50 values were estimated to be 20.32 ng/mL for parathion, 21.44 ng/mL for methyl-parathion, 42.15 ng/mL for fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…The broad-selectivity of this MAb was probably due to the involved strategy of heterologous screening for hybridomas instead of the homologous one. Previous researches Muldoon et al, 2000;Wang et al, 2010) also indicated that application of this screening strategy increased the likelihood of isolating hybridomas secreting very broad-specific MAbs.…”
Section: Assay Selectivitymentioning
confidence: 95%
See 1 more Smart Citation
“…The broad-selectivity of this MAb was probably due to the involved strategy of heterologous screening for hybridomas instead of the homologous one. Previous researches Muldoon et al, 2000;Wang et al, 2010) also indicated that application of this screening strategy increased the likelihood of isolating hybridomas secreting very broad-specific MAbs.…”
Section: Assay Selectivitymentioning
confidence: 95%
“…Since hapten heterology is often employed to modify the performance of competitive immunoassay for small molecules (Kim et al, 2003;Wang et al, 2011), it can also be introduced into the steps of hybridoma selection. To date, using heterologous ELISAs for hybridoma screening is yet limited to very few kinds of MAb generation Muldoon et al, 2000;Shim et al, 2010;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of applications involving small and environmentally important toxic substances are: -cadmium [206] -PAHs, PCBs [207], dioxins [208] -organophosphorus pesticides [209,210] -pyrethroid pesticides in water [211] -mycotoxins [212] and bacterial toxins [213] -the wood preservative pentachlorphenol (PCP) in soil [214] -explosives [215] -chemical warfare agents [216] …”
Section: Markers For Environmental Chemical Exposurementioning
confidence: 99%
“…To achieve this goal, the generation of an antibody with class-specificity is necessary, in addition to the development of multi-label and multiplex techniques (Franek et al, 2006). Until now, extensive effort has been devoted to developing antibodies that are class-specific to chemical contaminants, e.g., sulphonamides (Adrian et al, 2009;Pastor-Navarro et al, 2009), fluoroquinolones (Pinacho et al, 2012;Wang et al, 2007) and organophosphates (Piao et al, 2009;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%